Separation and determination of flavonoids in three traditional chinese medicines by capillary electrophoresis with amperometric detection. Issue 7 (29th February 2016) - Wang, Wei; Lin, Ping; Ma, Lihong; Xu, Kaixuan; Lin, Xiuli
Abstract : Flavonoids are important active ingredients in many traditional Chinese medicines. In this paper, capillary electrophoresis with amperometric detection was employed to separate and detect eight flavonoids, rutin, quercetrin, quercetin, kaempferol, kaempferide, catechin, apigenin, and luteolin, in a home‐made capillary electrophoresis device. Under the separation voltage of 2000 V, the eight flavonoids could be completely separated within 33 min in 18 mM borax running buffer at pH 10.2. Good linear relationships were obtained for all analytes and the detection limits for flavonoids ranged from 0.46 to 0.85 μM. Then, the method was applied to separate and determine the flavonoids in three traditional Chinese medicines, hippophae rhamnoides, hypericum perforatum, and cacumen platycladi. Finally, rutin, kaempferol, quercetin, and quercetrin were discovered in these medicines and the concentrations ranged from 0.28 to 9.94 mg/g. The recoveries of flavonoids ranged from 84.7 to 113%, which showed the high reliability of this method.